Menemukan Cahaya dalam Kegelapan Berdasarkan Ratapan 3:1-24 - Dirman Solikhin Rohit Samaloisa; Anggi Laurencia; Malik Bambangan (Jurnal Riset Rumpun Agama dan Filsafat, 2026)
This research is motivated by the reality of human life that is inseparable from suffering and a crisis of hope, particularly within the context of faith experiences. Lamentations 3:1–24 was chosen as the object of study because it contains a profound expression of suffering that transforms into hope through an awareness of God's steadfast love. The purpose of this study is to theologically examine the meaning of hope amid suffering and to explore how this text provides spiritual strength for believers in the contemporary era. The research employs a qualitative method with a library research approach and theological-biblical hermeneutical analysis of the text of Lamentations 3:1–24. The novelty of this research lies in its integrative interpretation, which emphasizes existential honesty, faith reflection, and spiritual refinement as a path to forming spiritual character through suffering. The findings indicate that suffering is not the end but a divine means to direct believers toward true hope in God’s steadfast love. Thus, honest faith, prayer, and waiting become tangible expressions of a spirituality that endures and grows amid darkness.